Identifikasi Penyebab Kecacatan Kemasan Minyak Kelapa Sawit Menggunakan Metode FMEA dan FTA Pada Departemen Shortening (Studi Kasus: PT. XYZ) - Amiril Mukminin; Said Salim Dahda (Jurnal Serambi Engineering, 2022)
Quality control is a part that must be taken into account by every company in a developing era like today. Pt. XYZ is a company that produces palm oil. Types of defects in the packaging in PT. XYZ includes uneven packaging prints, packaging not tightly closed, peeling brand glue. From the three packaging defects, an analysis was carried out using the FMEA and FTA methods so that the quality of the product was even better by providing proposed improvements at the stage that was considered a failure. The highest RPN value is in the defect of peeling brand glue, with an RPN value of 168, the number of defects in a period of 6 months is 3949 pcs. This is carried out by FTA analysis so that the cause is known to be the lack of rest hours for workers, stuffy rooms, the absence of comfortable facilities, and workers must complete their work quickly so that it requires very extra accuracy. The proposed improvements for peeling brand glue are to provide sufficient rest hours, provide special training to workers, change the layout of the room or add a room so that it is not stuffy, and facilitate a blower or fan that is sufficient for the glue to dry quickly.